2018
DOI: 10.1101/304618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The alkyl side chain of PACA nanoparticles dictates the impact on cellular stress responses and the mode of particle-induced cell death

Abstract: For optimal exploitation of nanoparticles (NPs) in biomedicine, and to predict nanotoxicity, detailed knowledge on the cellular responses to cell-bound or internalized NPs is imperative.The outcome of NP-cell interaction is dictated by the type and magnitude of the NP insult and the cellular response. Here, we have systematically studied the impact of minor differences in NP composition on cellular stress responses and viability by using highly similar poly(alkylcyanoacrylate) (PACA) particles. Surprisingly, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it has been seen recently that PBCA NPs could present potential toxicity, which could be attributed to faster degradation and a more rapid release of degradation products [78]. However, other authors have demonstrated that they can induce oxidative stress, ferroptosis and necrosis [79].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Moreover, it has been seen recently that PBCA NPs could present potential toxicity, which could be attributed to faster degradation and a more rapid release of degradation products [78]. However, other authors have demonstrated that they can induce oxidative stress, ferroptosis and necrosis [79].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%